2009
DOI: 10.1007/s10562-009-0121-x
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Aerobic Oxidation of Cyclohexane and Ethyl Benzene Over Chromium-Containing Mesoporous Organosilicas

Abstract: Chromium-containing ethane-bridged hybrid periodic mesoporous organosilicas (Cr-PMO) were synthesized using 1,2-bis(triethoxysilyl)ethane (BTEE) and tetraethyl orthosilicate (TEOS) as silica sources and alkyltrimethyl ammonium salts as surfactants by two different synthesis routes. PXRD and N 2 adsorption-desorption analysis shows that the original structure of the materials is maintained after chromium substitution while spectroscopic study proves the incorporation of chromium in the frame wall positions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…60 The oxidation of CH with molecular oxygen (air) over mesoporous metal silicate catalysts has been extensively explored. [61][62][63][64][65][66] Table 2 presents a short summary of the results published in the literature. The sponge-like material Co-TUD-1 was shown to be an active and selective catalyst for the…”
Section: Oxidation Of Alkanesmentioning
confidence: 99%
“…60 The oxidation of CH with molecular oxygen (air) over mesoporous metal silicate catalysts has been extensively explored. [61][62][63][64][65][66] Table 2 presents a short summary of the results published in the literature. The sponge-like material Co-TUD-1 was shown to be an active and selective catalyst for the…”
Section: Oxidation Of Alkanesmentioning
confidence: 99%
“…Table compares the results of the present work with those for previously reported catalysts . The catalyst and method applied in the present case have advantages in terms of heterogeneous nature and better conversions, selectivity and reusability of the catalyst and separation of acetophenone.…”
Section: Resultsmentioning
confidence: 67%
“…Heterogeneous catalysts have become very important for ecofriendly industrial processes because these materials are developed with the objective of performing reactions under milder conditions and without hazardous wastes. Many researchers have used Cr(III)‐based heterogeneous catalysts for the oxidation of ethylbenzene using various oxidants . Dapurkar et al .…”
Section: Introductionmentioning
confidence: 99%
“…In 1940's, the pioneering work on the oxidation of para-substituted ethylbenzene into corresponding acetophenone with air in the presence of Cr2O3 at 403 -433 K was reported [24]. Recently, it was found that supported Cr2O3 [25,26] and Cr 3+ -containing mesoporous materials [27][28][29] and metal-organic framework (Cr-MIL-101, Ref. [30]) effectively promoted oxidation of benzyl alcohol to benzaldehyde [25], cycloalkanes to α,β-unsaturated ketones [28,30], monoterpenic alkenes to epoxide and allylic derivatives [27,30], and autooxidation of cyclohexane into cyclohexanone and cyclohexanol [26,29] in an O2 or air atmosphere.…”
Section: Introductionmentioning
confidence: 99%